2017
DOI: 10.1002/smll.201603990
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Responsive Dual Aptamers‐Targeted Bubble‐Generating Nanosystem for Cancer Triplex Therapy and Ultrasound Imaging

Abstract: The absence of targeted, single treatment methods produces low therapeutic value for treating cancers. To increase the accumulation of drugs in tumors and improve the treatment effectiveness, near-infrared 808 nm photothermal responsive dual aptamers-targeted docetaxel (DTX)-containing nanoparticles is proposed. In this system, DTX and NH HCO are loaded in thermosensitive liposomes. The surface of liposomes is coated with gold nanoshells and connected with sulfydryl (SH) modified AS1411 and S2.2 aptamers. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 36 publications
1
56
0
Order By: Relevance
“…The preformed liposomes were mixed with gold salt to form a uniformly distributed Au shell on the liposomes′ surfaces, followed by sulfhydryl-aptamer coordination on the gold nanoparticle. These liposomes loaded with docetaxel and ammonium chloride, with dual ligand functionalization, significantly increased cellular uptake in breast cancer cell line (MCF-7) cells and showed higher tumor suppression compared to single targeting by one aptamer [226].…”
Section: Sulfhydryl-aptamer Gold Coordinationmentioning
confidence: 99%
“…The preformed liposomes were mixed with gold salt to form a uniformly distributed Au shell on the liposomes′ surfaces, followed by sulfhydryl-aptamer coordination on the gold nanoparticle. These liposomes loaded with docetaxel and ammonium chloride, with dual ligand functionalization, significantly increased cellular uptake in breast cancer cell line (MCF-7) cells and showed higher tumor suppression compared to single targeting by one aptamer [226].…”
Section: Sulfhydryl-aptamer Gold Coordinationmentioning
confidence: 99%
“…Upon interaction with serum and stroma in blood and tissue, some physiochemical properties of the nanocarriers will be altered and weakened, leading to invalidation of some biological effects. The “smart” nanosystems refer to a class of nanocarriers which can harness physiological cues for tumor cell targeting and desired release behaviors, such as activated cellular uptake or stimuli‐responsive drug release . The difference between the “smart” and “nonsmart” materials, as shown in Figure , is defined by its response to the biological barriers in vivo.…”
Section: Nanomaterials For Cancer Precision Therapymentioning
confidence: 99%
“…Both type of bubbles contain octafluoropropane gas, while Definity uses a phospholipid spherical shell and Optison an albumin based shell to enclose the gas. Experimentally, SPIONs, liposomes, AuNPs, and nanodroplets have also been evaluated as contrast agents and drug carriers during NP-based US applications [353,354,355,356,357,358]. All types of microbubbles can serve as platforms for not only imaging, but also for the distribution of drugs for therapy by encapsulating the drug into the bubbles [359,360].…”
Section: Multimodal Imaging Options For Prostate and Breast Cancermentioning
confidence: 99%
“…The authors concluded that the gene-transfection efficiency was better than that of a liposomes-based comparable system, and that their microbubble system could be used as a gene-loading and ultrasound-imaging technique of tumors. For BC, Zhao et al recently investigated a near-infrared (808 nm) photothermal responsive dual aptamers-targeted docetaxel-containing NPs for both cancer therapy and USI [353]. The dual-ligand functionalization increased uptake in MCF-7 cells and made USI possible at tumor site.…”
Section: Multimodal Imaging Options For Prostate and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation